Can Photographs in The Sustainability Report Obfuscate Negative Environmental Issues? Evidence from Indonesia - Pujiningsih, Sri; Pambudi, Fickry Styo (Indonesian Journal of Sustainability Accounting and Management, 2024)
This study aims to discover the motivation for and use of photography in sustainability reports. This study examined 267 photographs from PT Freeport Indonesia’s (PTFI) sustainability report using a content analysis approach. Photographs were interpreted according to the impression management theory. The number of environmentally related photographs had decreased, and they were displayed the least. The predominance of photographs of social activities was allegedly used by PTFI to obscure or cover up its poor environmental performance. In comparison to places and objects, photographs of people were displayed the most. Repeated images of happy people’s expressions were used as a visual rhetorical impression management technique that tapped into readers’ emotions to enhance the company’s image and legitimacy. This research has implications for companies to be more transparent in disclosing photos related to environmental issues. The social implication of this research is that people have to be more careful and critical, not just take the impression of the photos conveyed by the company. The findings of this study enlighten and raise awareness that photographs in sustainability reports are used as rhetorical and impression management tools to boost image and legitimacy.